Solar-Wind Hybrid Power Generation System Planning In Kijing Beach, West Kalimantan - Verdian, Rifqi Azzumardi; Hiendro, Ayong; Khwee, Kho Hie (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
PLN finds it difficult to meet the electricity needs of the entire Indonesian population. Therefore, it is necessary to develop and optimize New Renewable Energy (EBT) such as solar energy, ocean energy, geothermal, and hydropower. This research uses secondary data that can be accounted for and uses Homer Energy Modeling software to analyze the use of available energy. This research analyzes the planning of a hybrid power plant that uses wind and solar power to meet energy needs in Kijing Beach from an economic perspective. From the simulations conducted, the analysis results show that the configuration of solar panels "“ wind turbine- inverter - battery in the off grid system results in a total overall cost of Rp2,627,560,16.36.